The Solubility of Gases in Metals - V. H. Gottschalk (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
THE solubility of gases in metals has been of interest since Graham's time in 1866, but, although the subject was actively studied by iron and steel metallurgists during the eighties, the era of painstaking laboratory investigation begins in 1907 with the publication of Sieverts'1 thesis on the occlusion and diffusion of gases in metals. Since then, Sieverts has worked almost continuously in this field, and his views on the subject are the prevailing ones at the present time.2 Probably the most important result obtained by Sieverts, and frequently verified since by other observers, is the discovery that at a constant temperature the solubility of almost all gases in both the liquid and solid state of most of the metals is proportional to the square root of the pressure (for pressure above 100 mm.). The obvious explanation of this fact is that the gas dissolves as atoms and not as molecules, although it has been pointed out a number of times, first by Donnan and Shawl in connection with their work on the solubility of oxygen in silver at 1075° C., that the formation and solution of a compound of the metal and gas would also be indicated by a variation of the solubility with the square or higher root of the pressure. Sieverts4 himself raised the question whether the usual explanation (i. e., that the gas dissolves as atoms) may not be wrong, when he found that the square root law held also for the solubility of sulfur dioxide in molten copper; in which case dissociation into simpler molecules or atoms does not take place. Stubbs5 subsequently showed that Sieverts and Krumbhaar's "constant" for sulfur